Effects of yoga on impulsivity in patients with and without mental disorders: a systematic review - Yuri de Castro Machado; Mariana Oliveira; Jogiely Larissa Ferreira Lima; Hemant Bhargav; Shivarama Varambally; Débora Marques de Miranda; Marco Aurélio Romano-Silva (BMC Psychiatry)
Abstract Background Yoga can be used as a complementary intervention to conventional treatments, whether pharmacological or non-pharmacological. Sustained practice of yoga can generate a series of benefits for individuals' quality of life and improve their physical fitness. Objective To investigate the potential effects of yoga as an adjunct intervention in conditions involving impulse control issues, such as attention deficit hyperactivity disorder (ADHD), borderline personality disorder, bipolar affective disorder, and substance use disorders. Methods We performed a systematic review of placebo-controlled, randomized trials of yoga in patients with impulsivity. PubMed, Web of Science, and Science Direct databases were searched for trials published up to January, 2023. Data were extracted from published reports and quality assessment was performed per Cochrane recommendations. Results Out of 277 database results, 6 RCT were included in this systematic review. To assess the level of attention and impulsiveness, the following scales were analyzed: Barratt Impulsiveness, UPPS-P Impulsive Behavior scale, Conners’ Continuous Performance Test IIª and Conners’ Parent Rating Scale–Revised: Long. Conclusions Yoga didn’t have a significant improvement in impulsivity when compared to placebo. There are many tools to assess impulsivity, but they mean different concepts and domains consisting in a weakness on comparison of yoga effects. PROSPERO registration CRD42023389088.